The Modernity and Religious Practices: A Sociological Analysis of the State Islamic University of North Sumatra Students from the 2021–2023 Cohorts - Khoidir Khoidir; Wirman Wirman (Bulletin of Indonesian Islamic Studies, 2025)
This study aims to analyze the influence of modernity on religious practices among students of the State Islamic University of North Sumatra (UINSU) from the 2021–2023 cohorts. Modernity, characterized by the advancement of science, technology, and digital culture, has significantly impacted students’ religious understanding, practices, and the authority of religion. This research employs a qualitative approach using purposive sampling with three participants representing each cohort (2021, 2022, and 2023). Data were collected through in-depth interviews, participatory observation, and document studies, and were analyzed thematically. The findings reveal that modernity presents both opportunities and challenges. On the one hand, digital technology facilitates access to religious information, expands the scope of da’wah, and supports worship practices through reminder applications and online lectures. On the other hand, modernity also creates distractions from social media, encourages individualism, and raises concerns about the validity of religious information. Students respond to these challenges with various strategies, including time management, selective use of technology, and strengthening spiritual awareness. Thus, modernity does not merely weaken religious practices but can also serve as a means of reinforcing religious identity when approached wisely.